Aflatoxin M1 contamination in grated parmesan cheese marketed in Rio de Janeiro - Brazil - Trombete,Felipe Machado (2014)
This study aimed to determine the occurrence of AFM1 contamination in the samples of grated parmesan cheese marketed in the Metropolitan Region of Rio de Janeiro -Brazil. Thirty samples representing 10 major brands marketed in the region were analyzed by High Performance Liquid Chromatography with fluorescence detection (HPLC-FLD) after purification with immunoaffinity column. The method showed recovery values within the range of 70-90%, with RSD lower than 15% and limits of detection and quantification below the maximum level allowed by the European Commission for the presence of AFM1 in cheeses. The mycotoxin was identified in 18 (60%) of the grated cheese samples tested. The highest value corresponded to 0.69 ± 0.02 µg/kg and the mean for all the analyzed samples was 0.16 µg/kg. All the samples were lower than the limit established by the Brazilian legislation (2.5 µg/kg) for AFM1 in cheeses in general. However, eight samples (26.7%) presented AFM1 levels above the tolerance limit of 0.25 µg/kg adopted by the European Commission. These results indicated that AFM1 levels in the grated cheese consumed in Rio de Janeiro -Brazil were relatively high and it could provide a potential hazard for the public health.